THE DEVELOPMENT OF TOURISM AS A NECESSARY FACTOR IN INCREASING COMPETITIVENESS AND STRENGTHENING THE CAPACITY TO COUNTERACT CRISES - Rano Farkhod kizi Otajonova (Galaxy International Interdisciplinary Research Journal, 2023)
The article examines the development of tourism in Uzbekistan, its state of development, opportunities and prospects as a factor of increasing competitiveness and strengthening the capacity to withstand crises.